SEXUAL NURSING CARE FOR THE POSTPARTUM PERIOD AND ITS IMPACT ON SEXUAL DYSFUNCTION AND LIFE SATISFACTION AMONG EGYPTIAN WOMEN - Nabila E. Sabola; Marwa A. Shahin; Khader, Khaled A; Hanan M. Metwally; Mervat M. Desoky (Malaysian Journal of Public Health Medicine, 2020)
Many couples experience postpartum period of decreasing sexual satisfaction. Postpartum sexual dysfunction is a very common and relevant clinical problem, with significant adverse effects on women's health. The aim of this study was to evaluate the impact of sexual nursing care for the postpartum period on sexual dysfunction and life satisfaction among Egyptian women. A quasi-experimental design was used to study 219 women selected using a purposive sample. The study was conducted in out-patients maternity clinic at Zagazig university hospitals, Sharkia Governorate, Egypt, between the periods from February 2019 to February 2020. Data was collected using three tools. The first: Structured interview questionnaire that consist from three parts, part one: socio demographic characteristics , part two obstetric history and part three sexual history, the second: Female Sexual dysfunction index (FSDI), and the third: Satisfaction with Life Scale (SWLS).Four session about sexual education was done. The Results showed an improvement in sexuality and life satisfaction after application of sexual nursing care for the postpartum period including kegel’s exercise, positioning and distractions techniques post intervention compared to pre intervention. The study concluded that sexual nursing intervention for postpartum period improve sexual functioning and create enjoyable intercourse and there was high positive correlation between sexuality and life satisfaction after implementation of the sexual nursing care intervention. The study recommended to provide counselling /training program about sexual nursing care intervention during postpartum period for nurses working in different health care settings.